PROMOSI KESEHATAN DENGAN PEMBERIAN JUS BAYAM MERAH (AMARANTHUS GANGETICUS) DALAM MENCEGAH ANEMIA PADA IBU HAMIL - Keleng Ate Ginting; Raini Panjaitan; Andreais Boffil Cholilullah (JURNAL PENGMAS KESTRA (JPK), 2021)
During pregnancy anemia often occurs, anemia is a term that is often used for a decrease in hemoglobin (Hb) levels. Anemia during pregnancy can increase the risk of death during childbirth, give birth to babies with low birth weight, miscarriage and increase the risk of premature birth. Health promotion activities through the provision of red spinach juice can be used as an alternative in socializing the prevention and treatment of anemia in pregnant women. The purpose of implementing community service is to maintain the health quality of pregnant women so that they are not at risk of anemia during pregnancy through health promotion and providing simple treatment through the provision of red spinach juice. This community service was carried out for two days at the Salma clinic, Perbaungan District. On the first day of the activity, starting from registration, checking hemoglobin levels before giving red spinach juice, delivering material, demonstration of making red spinach juice and giving red spinach juice. On the second day of implementation, checking hemoglobin levels to see changes in hemoglobin levels after giving spinach juice. red. The results of the examination of hemoglobin levels showed that the mean hemoglobin level before administration of red spinach juice to pregnant women was 10.30 and after administration of 10.89 with a median value before administration of 10.15 and after administration of 10.75, SD value before administration of 0. ,6 and the SD value after administration was 0.5 with a minimum hemoglobin level before administration of 10 and after administration of 10, the maximum hemoglobin level before administration was 12 and after administration was 13. Keywords: Health Promotion; Red Spinach; Hemoglobin Level; Anemia